Blending Study of Bio Oil and Light Fuel Oil - Sharifah Sarah bt Syed Jalil, Sharifah Sarah (Universiti Teknologi Petronas, 2011)
Bio oil, a liquid product from biomass via fast pyrolysis, presents a promising potential in substituting petroleum fuel. The sustainability and clean energy that bio oil promises makes it an attractive option. However, it has certain limitations that bring on many problems in its handling and utilization especially due to its high viscosity and water content. Thus, bio-oils require certain method to improve their characteristics before they can be used as a replacement for fuels. The objective of this project is to improve bio-oil by creating a stable emulsion through blending with light fuel oil. The bio oil utilized in this study is from empty fruit bunches (EFB), and the light fuel oil is No.2 diesel. The literature review includes the discussion on the fuel properties of bio oil, creating an emulsion and role of surfactant in emulsion stability. The methodology then describes two main parts of conducting the experiment- sample preparation and sample characterization. In sample preparation, the emulsion is prepared with four different bio oil/diesel initial weight ratio- 5% bio oil, 95% diesel; 10% bio oil, 90% diesel; 15% bio oil, 85% diesel and 20% bio oil, 80% diesel. The samples are then replicated but with the addition of Tween 80 as a surfactant. Stability of the samples are then observed. Sample are then being characterized based on fuel properties such as viscosity, water content, density and CHNS elemental analysis. Discussion on the effects of surfactant and the initial bio oil/diesel ratio is then explained in chapter 4. It is concluded that a surfactant is necessary to produce a more stable emulsion and the optimum bio oil/diesel initial weight ratio is 15:85.